(untitled) (Journal of Oriental Studies, 2016)
This article is destined for the concept of «hospitability» in Kazakh and Arab proverbs. It is relevant to both languages where a concept is closely related to the custom of Kazakh and Arab nations and it describes cultural linguistic model.